APLIKASI ALAT BANTU BELAJAR BAHASA INGGRIS UNTUK SEKOLAH DASAR: APLIKASI ALAT BANTU BELAJAR BAHASA INGGRIS UNTUK SEKOLAH DASAR - Nur Aini H; Hepnyi Samosir (Repository STMIK Prabumulih, 2021)
The application of learning aids is a component of the teaching delivery system that can be used to support learning activities, whether used by teachers or students. In an effort to improve the quality of good English education, especially for children who are applied at an early age, a very effective and efficient learning method is needed. For beginners or especially elementary school children, an interesting and fun English learning media is needed. This learning media innovation is used to improve the quality of learning. One of the technological products that can be used as an innovation in learning is a computer. In English learning media, elementary school (SD) children do not attract students' interest in learning English, based on this, the authors are interested in improving the quality of education, especially good English subjects, especially for students aged early, namely by building an English learning application for elementary schools. This application as a learning aid is a component of the teaching delivery system that can be used to support the learning process. The display is presented in the form of a combination of text, images, sound, and even videos. This application is made using Adobe Flash. The system development model used in this study is the system development method used in this study is the Classic Software Life Cycle (SCLD) or Waterfall model